STRATEGI KOMUNIKASI PEMASARAN KELOMPOK WANITA TANI “PUTRI KENCANA” DALAM UPAYA MENINGKATKAN PENJUALAN PRODUK OMAH KELOR MELALUI WORD OF MOUTH (The Commercium, 2022)
Word of Mouth marketing communication strategy is a strategy that is often considered effective because in the process there is an act of giving personal recommendations based on consumer experience after using a brand or service. The existence of obstacles in digital marketing is one of the reasons why KWT Putri Kencana implements the current Word Of Mouth marketing communication strategy. This study aims to determine the process of implementing the Word Of Mouth marketing communication strategy by KWT Putri Kencana in an effort to increase sales of Omah Moringa products. This research uses qualitative research with a case study approach. Elements of the Word Of Mouth marketing communication strategy in this study are talkers with experienced consumers and employees of the Department of Agriculture as influential people who are involved in recommending products to others. Topics that discuss product benefits. Tools with social media (instagram, facebook, and whatsapp), training and counseling, as well as exhibition events as a tool to spread the message. Taking part with KWT Putri Kencana who responded and explained directly to the public and consumer questions about Omah Kelor. And tracking with the Putri Kencana KWT who monitors consumer responses by communicating with each other, being open to receiving consumer responses verbally and electronically, and receiving consumer testimonials. The Word Of Mouth communication model in this study is Organic Word Of Mouth which occurs naturally by consumers who voluntarily recommend Omah Moringa products. The findings in this study are that there is still a negative stigma against Moringa and people's ignorance of Moringa product processing, making Omah Kelor as a means of educating the community. Word of Mouth marketing communication strategy which is also not enough to increase sales results.